Peran Reputasi Perusahaan dalam Membangun Kepercayaan Pelanggan Maskapai Penerbangan - Nurkholish Majid (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
Research purpose to eximne role Corporate Reputation to Customer Trust development through service, contribution and image indicators. Reserarch using quantitative method with sample Garuda Indonesia Airlines’s Customer. Result by using regression analysis shown that Corporate Reputation have role to increase Customer’s Trust. Service and Contribution as indicator so has contibution for Trust development among Customer of Airline Service. Although image indicator has no impact to customer trust development. Furthemore this study has implication to examine role Corporate Reputation and Trust for behavioral intention for future research